Mechanics of Replacing Benefit Systems with a Basic Income: Comparative Results from a Microsimulation Approach - James Browne; Herwig Immervoll (Institute of Labor Economics (IZA), 2017)
Recent debates of basic income (BI) proposals shine a useful spotlight on the challenges that traditional forms of income support are increasingly facing, and highlight gaps in social provisions that largely depend on income or employment status. A universal "no questions asked" public transfer would be simple and have the advantage that no-one would be left without support. But an unconditional payment to everyone at meaningful but fiscally realistic levels would likely require tax rises as well as reductions in existing benefits. We develop a comprehensive BI scenario that facilitates an assessment of the resulting fiscal and distributional effects in a comparative context, undertake a microsimulation study to quantify them, and propose a simple decomposition to identify the mechanisms that drive effects in different country contexts. Results illustrate the challenges, but also the strengths, of existing social protection systems. A BI would fix benefit coverage gaps that exist in many countries, but would require very substantial tax rises if it were to be set at a meaningful level. As support would not be targeted on those most in need, it would not be a cost-effective way of directly reducing income poverty.
Keywords: C81; D31; H22; H55; 330; basic income; targeting; individualisation; conditionality; microsimulation